Research and information management - Ferguson Publishing (New York : Ferguson, 2010)
'In today's information age, it is easy to feel bewildered by the vast amount of data that is readily available. The importance of research and knowing how to analyze information is essential in many careers. Research and Information Management, Third Edition helps students learn how to acquire and manage all types of information.'--Publisher's web site.
Welcome to the information age -- Acquiring research skills -- Evaluating information -- Now what do I do with it? -- Creating effective presentations and memos -- Making the presentation fit the data -- Staying sane in the information age.
Includes bibliographical references and index
Keywords: Information retrieval -- Juvenile literature; Research -- Methodology -- Juvenile literature; Business report writing -- Juvenile literature; Information retrieval; Research -- Methodology; Business communication